ENZYME DIGEST AND ACID HYDROLYZED INDEX OF PROTEIN QUALITY EVALUATION - H.Mohammadiha P. Mostafavi (Tehran University of Medical Sciences, 1984)
A pancreatopeptidase (Elastase) digest index was devised for a rapid and accurate estimation of protein quality. This index was calculated on the basis of all the amino acids released by an in-vitro Elastase digestion, acid hydrolyses of same sample and the residue of enzyme hydrolyzed. The amino acids were determined by Thin-Layer Chromatography. Samples used were cooked white kidneybeans, cooked and over-heated soybean powder, and skimmed milk powder. Good correlation was observed between elastase index value and their biological values reported in the literature from feeding trials. The pattern of aminoacids released by acid and by enzyme hydrolysis was about the same.